PENERAPAN MANAGEMEN STRATEGI KEPALA MADRASAH DALAM MENINGKATKAN KOMPETENSI PEDAGOGIC GURU DI MI MARAQITT’LIMAT SANTONG LOMBOK UTARA - wildan (eJurnal Al Musthafa, 2024)
Strategic management of education is the implementation of education related to all educational material needs which are at the same time related to all aspects that exist in the effort to provide education, which is directly related to the learning process, facilities, or facilities and infrastructure Strategic Management aims to direct all company resources to be aligned and effective in achieving company goals. In the world of education, management is indispensable, through strategic management can expand future opportunities and minimize realized risks. Therefore an organization, company or educational institution must have a leader (leader) to determine the direction, and goals of an organization by providing direction in creating a supportive work climate for the implementation of the overall management process Pedagogic competence is the ability of teachers in managing student learning In the field of education needed by a teacher, namely pedagogic competence in seeing the characteristics of students from various aspects of life, be it moral, emotional, or intellectual. And with the presence of pedagogic competence of teachers will increase the competence of teacher professionalism in teaching. This study uses a research approach with methods applied to collect data, namely observation, interviews, and documentation. While the data analysis techniques used are data collection, data reduction, analysis, data presentation, and drawing conclusions. While the technical validity of data is used data trianggulation, method trianggulation, and theory trianggulation. The data obtained in this study is the application of the strategy management of the head of the madrasah in improving the pedagogic competence of teachers is good, and as for what is obtained by teachers through efforts to implement the management of the strategy of the head of the madrasah in improving the pedagogic competence of teachers is categorized as good.